Evaluation of hybrid lighting of lightweight concrete with different amounts of A4b plastic optical fiber - Rodríguez-Silva, Gustavo (2021)
The objective of this research is to quantify the contribution of light produced by hybrid lighting through translucent concrete panels, as well as to specify the mechanical properties of lightweight translucent concrete. To obtain data, it was proceeded to design common concrete, to which polystyrene foam beads were added, in different dosages, until the designation of light concrete was achieved. Later, plastic optical fibers were added in its structure forming specimens which were tested by translucency and mechanical tests. The results obtained were lightweight concrete panels made at 3%, by volume, fiber optic with translucency of 0.165% and 6.89 lux on average. It was concluded that lightweight concrete offers good support for the installed optical fibers, offering acceptable mechanical characteristics up to a maximum of 4% added fiber.